Community Support for Low-Income Elementary School Students with a Winter Gear Drive under COVID 19 Constraints - Wentworth, Paige; Kuntz, Lois-Ann (Maine Policy Review, 2021)
Washington County has one of Maine’s highest rates of child poverty. Winter is especially difficult with below-freezing temperatures, higher fuel costs, and many seasonal tourism-related businesses closed. Typically local schools have collections of hats and gloves that children can share. With the 2020-2021 COVID-19 restrictions, children could not reuse winter gear from a shared box and, if they did not have their own winter gear, they were unable to participate in outside activities. Additionally, because of spacing constraints, schools were using gyms for classrooms not for physical activities, which doubly disadvantaged students without winter gear. This paper describes a university student winter gear project and underscores the need for policies supporting children in poverty.